2013
DOI: 10.1111/j.1532-849x.2012.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Length of Occlusal Support on Masticatory Function of Free‐End Removable Partial Dentures: Short‐Term Adaptation

Abstract: After a 1-week adaptation period to free-end RPDs with occlusal support lengths reduced to the premolars, participants were able to achieve adequate masticatory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 36 publications
(58 reference statements)
2
29
0
1
Order By: Relevance
“…19 In 4 studies X 50 was determined after a given number of chewing strokes; one study determined D 50 , which is equivalent to X 50 until swallowing. 22 Three studies 22,24,25 also reported on chewing frequency and 2 studies 23,26 on maximum bite force.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…19 In 4 studies X 50 was determined after a given number of chewing strokes; one study determined D 50 , which is equivalent to X 50 until swallowing. 22 Three studies 22,24,25 also reported on chewing frequency and 2 studies 23,26 on maximum bite force.…”
Section: Resultsmentioning
confidence: 99%
“…24 The study of Sánchez-Ayala et al 25 showed a more or less linear effect of decreasing chewing frequency with increasing number of artificial teeth added on the RDP, in that study with an opposing maxillary complete denture.…”
Section: Page 9 Of 25mentioning
confidence: 89%
See 3 more Smart Citations